Tungsten heavy alloys with molybdenum, Y₂O₃ and lanthanum. A review - Lakshmi Prasad, B.S.; Raja Annamalai, A. (Сверхтвердые материалы, 2019)
The consolidated results of studies of tungsten doping with various metals and compounds (Ni, Fe, Cu, Mo, Y₂O₃, La₂O₃) are presented, the advantages of doping with regard to its conditions, microwave and plasma sintering techniques are shown. It has been found that the mechanical properties of tungsten are significantly improved by the addition of the above elements. The resulting heavy fame tungsten can be used to protect against nuclear radiation Представлено консолідовані результати досліджень легування вольфраму різними металами і сполуками (Ni, Fe, Cu, Mo, Y₂O₃, La₂O₃), показано переваги легування з урахуванням його умов, техніки мікрохвильового і плазмового спікання. Виявлено, що механічні властивості вольфраму значно покращилися при додаванні вищевказаних елементів. Отримані важкі слави вольфраму можуть бути використані для захисту від ядерного випромінювання. Представлены консолидированые результаты исследований легирования вольфрама различными металлами и соединениями (Ni, Fe, Cu, Mo, Y₂O₃, La₂O₃), показаны преимущества легирования с учетом его условий, техники микроволнового и плазменного спекания. Обнаружено, что механические свойства вольфрама значительно улучшились при добавлении вышеуказанных элементов. Полученные тяжелые славы вольфрама могут быть использованы для защиты от ядерного излучения.